The Role of Knowledge Sharing in Enhancing Employee Work Motivation - Dio Alfarago (LP3M Universitas Putra Bangsa, 2025)
Employee motivation is widely recognized as a fundamental component of organizational success, with knowledge-sharing activities serving as a significant contributory factor. This study examines the impact of knowledge-sharing activities on employee motivation by applying Vroom’s motivation theory. Using a quantitative approach with a survey research design, data were collected from 67 employees of PT. Midi Utama Indonesia Tbk, Medan Branch, selected from a total population of 200 using the Taro Yamane formula. The data were analyzed through linear regression to determine the relationship between knowledge-sharing and motivation. The findings reveal that knowledge-sharing activities significantly enhance employee motivation, highlighting their importance in fostering a productive and engaged workforce